Francis : Bishop of Rome: Second Edition - Collins, Michael (Book collections on Project MUSE., 2015)
In Francis: Bishop of Rome, Fr. Michael Collins introduced readers to the pope who has grabbed the attention and the spiritual imaginations of Catholics and others around the world. Now, in this second edition, Collins takes account of the most important events and development of his remarkable pontificate. With a focus on compassion, Francis has challenged world leaders to be more attentive to the poor, begun important reforms of the Curia and the Vatican Bank, and called for two synods of bishops to discuss pastoral challenges that face modern families. This new edition, which is 25% longer than the first, includes more details about Jorge Bergoglio's early life and a far more expansive understanding of the pontificate of this remarkable spiritual leader. People of God is a series of inspiring biographies for the general reader. Each volume offers a compelling and honest narrative of the life of an important twentieth or twenty-first century Catholic. Some living and some now deceased, each of these women and men has known challenges and weaknesses familiar to most of us but responded to them in ways that call us to our own forms of heroism. Each offers a credible and concrete witness of faith, hope, and love to people of our own day.